In-Season Prediction of Corn Yield Using Plant Height under Major Production Systems - Yin, Xinhua; McClure, M. Angela; Jaja, Ngowari; Tyler, Donald D; Hayes, Robert M (Agronomy journal, 2011)
The relationship between corn (Zea mays L.) yield and plant height has been poorly documented in major corn production systems. This study was conducted to assess the relationship of corn yield with plant height under four major corn production systems at Milan, TN from 2008 through 2010. Six N treatments at rates of 0, 62, 123, 185, 247, and 308 kg N ha−1 with four replications were evaluated in a randomized complete block design in the following corn production systems: nonirrigated corn after corn, nonirrigated corn after soybean [Glycine max (L.) Merr.], nonirrigated corn after cotton [Gossypium hirsutum (L.)], and irrigated corn after soybean. The regression of corn yield with plant height was significant and positive at 6-leaf growth stage (V6), 10-leaf growth stage (V10), and 12-leaf growth stage (V12), and mostly became stronger as plant growth progressed from V6 to V10 and to V12 under an exponential model in the four corn production systems for all 3 yr. In general, corn yield was strongly related with plant height measurements made at V10 and V12. Factors affecting the responses of plant height measured at V6, V10, and V12 or/and yield to the N treatments may have contributed to the variations of determination coeffient (R 2) values across years. In conclusion, corn yield may be predicted with plant height measurements collected during V10 to V12. This prediction provides a physiological basis for the utilization of high resolution plant height measurements to guide variable-rate N applications within the field on corn at around V10 and to more accurately estimate yield for earlier grain marketing purposes.